Techno-environmental assessment of a micro-cogeneration system based on natural gas for residential application - Colmenares-Quintero, Ramón Fernando (CT&F - Ciencia, Tecnología y Futuro, 2018)
The study carried out here aims to determine the advantage of using in-situ electricity generation facilities versus conventional generators, being evaluated from the environmental point of view. For this, an environmental analysis on the production of CO2 has been applied to two scenarios of electricity generation for a residential building in Medellin city (Colombia). The first one refers to La Sierra thermo-electric plant located in La Sierra, municipality of Puerto Nare, in the Antioquiashire, which is the most efficient plant in Colombian thermal generation. The second comparison scenario refers to the annual operation of a micro-cogeneration facility, which satisfies the building’s hot water and electrical energy needs. Using the capabilities of the TRNSYS v17® energy simulation software and the emission equations available in the public domain, the comparative environmental analysis is carried out between one and the other for the same load. The losses in electric transmission are assumed to be 10%. This analysis has shown a difference of more than 50% in emissions generation, with the main cause being the amount of fuel used, which for both cases is natural gas. On the other hand, this study shows the environmental advantages in the use of in-situ generators, decreasing transmission losses.